The Vaccination of Covid-19 for Community in Tasikmalaya - Miftahul Falah; Hani Handayani; Saryomo Saryomo; Oni Sahroni; Asep Setiawan; Yuyun Solihatin; Ida Herdiani; Bayu Brahmantia; Neni Sholihat; Hana Ariyani; Ali Firdaus; Rusdiana Rusdiana; Yusuf R. Romli; Rany Tien; Zainal Muttaqin; Ikhsan Ikhsan; Indra Gunawan; Ijang Budiana; Titin Suhartini (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The Covid-19 pandemic has created an emergency status in Indonesia. Through Presidential Decree No. 11 of 2020, Indonesia has declared a health emergency status. Various efforts have been made to overcome the impact of the Covid-19 pandemic, vaccination is one of efforts to solve the problem. The purpose of this community service is to implement a Covid-19 vaccination in the work area of ​​the Tamansari Public Health Center, Tasikmalaya City. The method used interviews followed by administering the Covid-19 vaccine to people who already meet the criteria. The total respondents in the Covid-19 vaccination were 804 people, which were carried out in two sessions. The implementation of Covid-19 vaccination was conducted at the Muhammadiyah University of Tasikamalaya with a total of 304 people in season 1 and 500 people in season 2. The community response was positive and supported the vaccination activities organized by UMTAS and Tamansari Public Health Center, Tasikmalaya City. In summary, people who got a vaccination of Covid-19 will increase individual and communal immunity.